2002
DOI: 10.1071/ar01103
|View full text |Cite
|
Sign up to set email alerts
|

Viruses infecting winter tomato crops in the North West Frontier Province of Pakistan

Abstract: Malakand Agency is a unique production area in the North West Frontier Province (NWFP) of Pakistan that is frost-free and in which tomato is grown as a winter crop. Tomato production in this area has been affected by virus-like diseases for the last 10 years. Tomato nurseries and fields at 11 locations in Malakand Agency were surveyed for tomato viruses during 1994–95. A total of 1071 samples from nurseries and 5083 samples from 142 fields were tested by indirect enzyme-linked immunosorbent assay (ELISA). In n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…These genotypes also showed resistance in the field as well as through aphid transmission and supported a low level of M. persicae population, except the TMS-1 genotype of S. lycopersicum which supported high population levels of M. persicae in both years but showed a low level of disease. Previous studies have demonstrated that sources of resistance or tolerance to CMV exist in S. lycopersicum, S. pimpinellifolium L., S. peruvianum L., S. habrochaites, S. cheesmaniae, S. chilense and S. lycopersicodies (Phills et al 1977;Gebre et al 1990;Nitzany 1992;Stoimenova et al 1992;Stamova 1993;Parella et al 1997;Abad et al 2000;Stamova and Chetelat 2000;Ali and Hassan 2002;Cillo et al 2007). The present study showed that these genotypes resist not only vector transmission but also the virus, and supports the findings of Pioven et al (1995) who demonstrated that virus resistance may exist at two levels i.e., against pathogen entry and/or at the level of systemic spread.…”
Section: Discussionmentioning
confidence: 95%
“…These genotypes also showed resistance in the field as well as through aphid transmission and supported a low level of M. persicae population, except the TMS-1 genotype of S. lycopersicum which supported high population levels of M. persicae in both years but showed a low level of disease. Previous studies have demonstrated that sources of resistance or tolerance to CMV exist in S. lycopersicum, S. pimpinellifolium L., S. peruvianum L., S. habrochaites, S. cheesmaniae, S. chilense and S. lycopersicodies (Phills et al 1977;Gebre et al 1990;Nitzany 1992;Stoimenova et al 1992;Stamova 1993;Parella et al 1997;Abad et al 2000;Stamova and Chetelat 2000;Ali and Hassan 2002;Cillo et al 2007). The present study showed that these genotypes resist not only vector transmission but also the virus, and supports the findings of Pioven et al (1995) who demonstrated that virus resistance may exist at two levels i.e., against pathogen entry and/or at the level of systemic spread.…”
Section: Discussionmentioning
confidence: 95%
“…In nurseries, three viruses, PVX, PVY and ToMV were detected with an incidence range of 9. 8 -22.3, 0 -36.6, and 16.5 -51.3%, respectively. In the field, five viruses [CMV, PVX, PVY, ToMV, and Tomato yellow top virus (TYTV)] were frequently found with an incidence range of 0 -13.3%, 2.6 -16.7%, 0.4 -13.8%, 26.1 -41.3%, and 1.7 -11.3%, respectively (Ali & Hassan 2002). In the current study, CMV was found to be the fourth prevalent virus in infected plants.…”
Section: Discussionmentioning
confidence: 99%